Heminephrectomy for Obstructed Upper Moiety in a Bilateral Duplex System - Christian A. Agbo; Sunday A. Tarkehe (International Journal of Medicine and Health Development)
The duplex kidney system is a rare congenital anomaly associated with accompanying problems that can threaten kidney function. A 50-year-old woman presented to our clinic with recurrent right flank pain of one year duration. Physical examination revealed right loin fullness with a ballotable right kidney. Computed tomography urography revealed a bilateral double collecting system with a dilated upper collecting system, worse on the right. Serum electrolytes, urea, and creatinine values were normal. The patient underwent right heminephrectomy, and stenting of the ureters was done bilaterally, with a satisfactory post-operative outcome. This case represents one of the rare urologic conditions diagnosed in our facility. Therefore, it underscores the relevance of this report in improving awareness regarding its presentation and management approach.